XTRA study protocol: eXploring medical sTudents' caReer reAdiness—a cross-sectional study in the UK. Issue 2 (4th April 2022) - Godoi, Amanda; McDade-Kumar, Mia; Virk, Farazi; Casteleyn, Charlotte; Marei, Omar; Yang, Ting; Moussa, Ahmed; Aman, Kashif; Byrne, Matthew H V; Babu, Priya Rose; Trikha, Sanya; Bamdad, Kiana; et al.
Abstract: Background and objectives: Professional and career enhancing opportunities are essential for developing skills required for a successful career in medicine. Research to date has mainly focused on the extent to which medical schools prepare students for clinical work as junior doctors. However, there remains a need to ascertain how students prepare for their career and what facilitates or hinders learning regarding careers in medicine. The purpose of the XTRA study is to examine career readiness of medical students at UK universities and the support they receive during their studies regarding career planning. Methods: The eXploring medical sTudents' caReer reAdiness (XTRA) study is a national cross-sectional study of all medical students enrolled at a UK medical school. Data collection will occur via a secure online survey designed as a training need analysis based on the principles of Super's theory (Super, 1953) of career development. A snowball sampling strategy will be used to recruit participants via social media and networks. Results will be analysed using quantitative analysis and thematic analysis to identify themes in qualitative responses. The primary outcome is to understand the perspective of current medical students on how well prepared they are about entering their careers in healthcare. Conclusions: We anticipate that findings from this study will help identify career readiness of medical students to facilitate the development of career development programmes and resources to ensure medical students are well equipped for their future careers.